Immune gene patterns and characterization of the tumor immune microenvironment associated with cancer immunotherapy efficacy. Issue 3 (March 2023) - Lin, Lili; Zhang, Wenda; Chen, Yongjian; Ren, Wei; Zhao, Jianli; Ouyang, Wenhao; He, Zifan; Su, Weifeng; Yao, Herui; Yu, Yunfang
Abstract: Although immunotherapy has revolutionized cancer management, most patients do not derive benefits from it. Aiming to explore an appropriate strategy for immunotherapy efficacy prediction, we collected 6251 patients' transcriptome data from multicohort population and analyzed the data using a machine learning algorithm. In this study, we found that patients from three immune gene clusters had different overall survival when treated with immunotherapy ( P < 0.001), and that these clusters had differential states of hypoxia scores and metabolism functions. The immune gene score showed good immunotherapy efficacy prediction (AUC was 0.737 at 20 months), which was well validated. The immune gene score, tumor mutation burden, and long non-coding RNA score were further combined to build a tumor immune microenvironment signature, which correlated more strongly with overall survival (AUC, 0.814 at 20 months) than when using a single variable. Thus, we recommend using the characterization of the tumor immune microenvironment associated with immunotherapy efficacy via a multi-omics analysis of cancer.